Biologia de aphis gossypii em plantas infectadas pelo vírus do mosaico das nervuras do algodoeiro - Michelotto, Marcos Doniseti; Busoli, Antonio Carlos [UNESP] (My University, 2009)
The objective of this work was to study the biology of cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae) on cotton plants (Gossypium hirsutum L.) healthy and infected by cotton vein mosaic virus. The assay was performed in climatic chambers at 25±1°C, under relative humidity of 70±10% and photophase of 12h. The treatments corresponded to aphids fed on leaves of healthy and infected by virus plants. Cages consisted of Petri dishes containing agar-water (1%) solidified and one leaf disc from either healthy or infected plants. Aphids fed on infected cotton plant had a significantly shorter nymphal phase (4.5 days) than aphids fed on noninfected cotton plant (4.9 days). No significant differences were observed in A. gossypii prereproductive, reproductive and postreproductive periods and longevity when fed on infected or noninfected plants. The highest mortality rate of aphids occurred on infected plants. The time interval between generations (T) and the time needed for the population to double in size (TD) were lower for aphids feeding on infected plants (9.74 and 1.66 days, respectively). The net reproductive rate (Ro), the intrinsic rate of population increase (rm) and finite rate of increase (λ) were higher for aphids feeding on infected plants. Aphids that fed on noninfected cotton plants showed better indices of development. In the reproduction of aphids the best indices were observed in aphids kept in infected plants.
Biology of cotton aphid on plants infected by cotton vein mosaic virus
Keywords: Aphididae; Cotton aphid; Gossypium hirsutum; Life table; Vector